INFLUENCE OF LEADERSHIP, REWARD AND PUNISHMENT ON MILLENNIAL EMPLOYEE PERFORMANCE - Samson Laurens (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze (1) the influence of leadership on the performance of millennial employees, (2) the effect of rewards on the performance of millennial employees, (3) the effect of punishment on the performance of millennial employees and (4) the influence of leadership, reward and punishment on the performance of millennial employees. The study was conducted at the BRI Ambon Branch Office for 2 (two) months, from March to April 2022. The population used in this study were all 54 millennial employees of the BRI Ambon Branch Office. Due to the relatively small number of samples (less than 100 people) and easily accessible by researchers, a saturated sample was determined. The results of the study conclude that (1) leadership has no significant effect on the performance of millennial employees, (2) rewards have no significant effect on the performance of millennial employees, (3) punishment has a positive and significant effect on the performance of millennial employees and (4) Leadership, reward and punishment have an effect on positive and significant impact on the performance of millennial employees of the BRI Ambon Branch Office.